ANALYSIS OF ENTREPRENEURIAL MANAGEMENT AND INNOVATION - Ganggali, Eynstein Abraham; Saerang, David Paul Elia; Mekel, Peggy Adeline (Universitas Sam Ratulangi, 2013)
The entrepreneurial management requires different management from the existing ones. But like the existing it requires systematic, organized, purposeful management. And while the ground rules are the same for every entrepreneurial organization, the existing business, the public-service institution, and the new venture present different challenges, have different problems, and have to guard against different degenerative tendencies. The purpose of this research is to analyze the practice of Entrepreneurship Management and Innovation to help Entrepreneur reach their business goal. This research uses qualitative approach and descriptive method, the analysis is a descriptive process, through literature study that collects information and classifying the data and then describing the variables. Results and conclusions are (1) that thenew functions of management that tap into the potential of all employees are: Energize, Empower, Support, and Communicate; (2) Entrepreneurial management requires policies and practices in four major areas, and (3) When innovation is perceived by the organization, this requires specific policies. It is recommended that students to have knowledge and ability, know how to manage people and be creative to create the organization or their job, and be innovative, make a different or very different. Keywords: entrepreneurship, entrepreneurial management, innovation